Report on the 17th Annual European CME Forum: Tomorrow’s World Today - Cara L. Macfarlane; Eugene Pozniak (Journal of CME)
The 17th Annual European CME Forum (17ECF) took place 6–8 November 2024 in Madrid, Spain. The meeting was subdivided into three main parts to address the theme “Tomorrow’s world today”: 1) GenAI and digital innovations; 2) Thriving today – anticipating tomorrow; 3) Tomorrow’s world today. As is customary, the Forum unofficially began with the pre-meeting sessions before being formally opened. This year’s pre-meeting sessions included a new “Core competencies in CME/CPD” track to address fundamental topics for the continuing medical education (CME) / continuing professional development (CPD) professional, as well as sessions led by key stakeholder groups in Europe. Throughout the two-day meeting, participants engaged in a series of interactive plenary sessions, workshops, breakouts and oral poster presentations led by European and international providers, accreditors, medical societies, grantors and learners. The Journal of CME also attended to discuss the 2024 Special Collection of articles, which covered the theme “AI innovations in lifelong learning: Revolutionising CME and CPD”. About 100 stakeholders participated in the annual meeting, with one-third attending for the first time. In keeping with the mission of European CME Forum, 17ECF aimed to facilitate education, interaction and engagement among all stakeholder groups with an interest in European and global CME and CPD, promoting multi-channel discussion in an independent and neutral environment.This meeting report summarises the meeting content and key takeaways from 17ECF.